Wykład do wyboru "Ocena kondycji finansowej przedsiębiorstwa" jako uzupełnienie przedmiotu "Sprawozdawczość i analiza finansowa" - Kowalak, Robert (The Election Lecture "The Opinion of Financial Condition of Enterprise" as Supplement of Lecture "The Reporting and Financial Analysis", 2005)
In 2001 at the University of Economy in Wrocław the election lecture "Opinion of financial condition of enterprise" was introduced. This lecture is the supplement of course lecture "Reporting and financial analysis". In this article the target of introduction of lecture, plan of lecture and themes are realized in within the limits of lecture are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 86-91